Dimensions of Vehicle Quality: Scale Development Study - Yildiz, Bülent; Çavdar, Ertuğrul (Bilturk, 2020)
The aim of this study was to develop a scale to evaluate vehicle quality (cars and light commercial vehicles). The study also compared owners’ assessment of the current status of their vehicles with the level of importance they assigned to the dimensions of vehicle quality. The sample consisted of 561 automobile owners. Data were collected using a questionnaire. Analysis revealed nine dimensions; reliability, user-friendliness, serviceability, performance, high-endness, aesthetics, perceived quality, comfort, and price. The gap between vehicle quality importance level and current vehicle status scores was greatest in the dimension “high-endness,” followed by serviceability, reliability, comfort, price, key features, user-friendliness, perceived quality, and “aesthetics.”
Keywords: İşletme; Vehicle quality; Qaulity Dimensions; Quality; Vehicle quality; Quality Dimensions; Quality; Business Administration; 11. Sustainability